Selenium enhances chilling stress tolerance in coffee species by modulating nutrient, carbohydrates, and amino acids content - de Sousa, Gustavo F.; Silva, Maila Adriely; de Morais, Everton G.; Van Opbergen, Gustavo Avelar Z.; Van Opbergen, Guilherme Gerrit A. Z.; de Oliveira, Raphael R.; Amaral, Douglas; Brown, Patrick; Chalfun-Junior, Antonio; Guilherme, Luiz Roberto Guimarães (Frontiers in Plant Science, 2022)
The effects of selenium (Se) on plant metabolism have been reported in several studies triggering plant tolerance to abiotic stresses, yet, the effects of Se on coffee plants under chilling stress are unclear. This study aimed to evaluate the effects of foliar Se application on coffee seedlings submitted to chilling stress and subsequent plant recovery. Two Coffea species, C. arabica cv. Arara and C. canephora clone 31, were submitted to foliar application of sodium selenate solution (0.4 mg plant-1) or a control foliar solution, then on day 2 plants were submitted to low-temperature (10°C day/4°C night) for two days. After that, the temperature was restored to optimal (25°C day/20°C night) for two days. Leaf samples were collected three times (before, during, and after the chilling stress) to perform analyses. After the chilling stress, visual leaf injury was observed in both species, however, the damage was 2-fold higher in C. canephora. The lower effect of cold on C. arabica was correlated to the increase in ascorbate peroxidase and higher content of starch, sucrose, and total soluble sugars compared with C. canephora, as well as a reduction in reducing sugars and proline content during the stress and rewarming. Selenium increased the nitrogen and sulfur content before stress but reduced their content during low-temperature. The reduced content of nitrogen and sulfur during stress indicates that they were remobilized to stem and roots. Selenium supply reduced the damage in C. canephora leaves by 24% compared with the control. However, there was no evidence of the Se effects on antioxidant enzymatic pathways or ROS activity during stress as previously reported in the literature. Se increased the content of catalase during the rewarming. Se foliar supply also increased starch, amino acids, and proline, which may have reduced symptom expression in C. canephora in response to low temperature. In conclusion, Se foliar application can be used as a strategy to improve coffee tolerance under low-temperature changing nutrient remobilization, carbohydrate metabolism, and catalase activity in response to rewarming stress, but C. arabica and C. canephora respond differently to chilling stress and Se supply.